Obesogenic Eating Behavior and Nutritional Status in Polycystic Ovary Syndrome Patients in Women of Childbearing Age at Harapan Kita Mother and Children's Hospital, Jakarta - Yulia Wahyuni; Desi Fitriani (East Asian Journal of Multidisciplinary Research, 2023)
Polycystic Ovary Syndrome (PCOS) affects the metabolic, endocrine and psychological systems. PCOS Mostly occurs in women of reproductive age. Problems with nutritional status in PCOS patients are supported by obesogenic eating behavior. This study aims to examine obesogenic eating behavior and nutritional status in PCOS patients. The type of research used is an analytical survey with a cross sectional study approach. This research was conducted at RSAB Harapan Kita. The sample for this study was women of childbearing age aged 20-35 years using a total sampling technique with a total sample of 33 people. Obesogenic dietary pattern data was obtained using SQFFQ (Semi Quantitative Food Frequency Questionnaire) and nutritional status was obtained by BMI/U by directly measuring body weight using a digital scale and height using a microtoa. Data analysis uses Pearson correlation analysis.